2021
DOI: 10.1016/j.jse.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical and radiographic outcomes of an augmented baseplate in reverse shoulder arthroplasty for glenohumeral arthritis with glenoid deformity

Abstract: Background: Glenoid deformity is commonly encountered in patients undergoing reverse shoulder arthroplasty (RSA). Augmented baseplates can correct glenoid deformity while potentially avoiding certain complications encountered with structural bone graft. Limited evidence exists to support the use of metallic augmented baseplates in RSA. Methods: We performed a retrospective review to identify all patients treated with an augmented baseplate during primary RSA with a minimum of 1 year of clinical and radiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In another retrospective descriptive analysis of 67 patients with Walch B2, B3, or C glenoids treated with the 8-degree posterior augmented baseplate, Virk et al demonstrated good functional outcomes, low rates of scapular notching, and no evidence of glenoid loosening with a mean follow-up of 3.3 years 55 . A review of 44 patients treated with half-wedge or full-wedge augmented baseplates further supports the favorable short-term functional outcomes reported in the preceding studies, although they did note an 11% rate of acromial stress fracture 53 .…”
Section: Augments In Rsasupporting
confidence: 64%
See 1 more Smart Citation
“…In another retrospective descriptive analysis of 67 patients with Walch B2, B3, or C glenoids treated with the 8-degree posterior augmented baseplate, Virk et al demonstrated good functional outcomes, low rates of scapular notching, and no evidence of glenoid loosening with a mean follow-up of 3.3 years 55 . A review of 44 patients treated with half-wedge or full-wedge augmented baseplates further supports the favorable short-term functional outcomes reported in the preceding studies, although they did note an 11% rate of acromial stress fracture 53 .…”
Section: Augments In Rsasupporting
confidence: 64%
“…At final follow-up, the posteriorly augmented group demonstrated superior shoulder function and greater active forward elevation compared with the superiorly augmented group. Although this study has been cited as evidence that posterior augments perform better than superior augments 53 , it is important to note that the analysis is essentially a comparison of 2 distinct indications for RSA. The group treated with superior augments for superior glenoid wear likely represented a cohort of patients with rotator cuff arthropathy, while the group treated with posterior augments for posterior glenoid wear likely represented a cohort of patients in which primary osteoarthritis was the predominant diagnosis.…”
Section: Augments In Rsamentioning
confidence: 99%
“…38 Clinically, both augmented constructs and autogenous bone grafting between the backside of the baseplate and the native glenoid have generally been associated with good clinical outcomes. 34,39 However, bone graft constructs are subject to resorption in some cases and are more at risk for micromotion compared with metallic offset. 40,41 One study suggested that baseplate failures were more common with higher degrees of preoperative deformity (226°in failures versus 215°in successes), although this difference did not reach statistical significance (P = .06).…”
Section: Reverse Shoulder Arthroplasty Considerationsmentioning
confidence: 99%
“…2 However, acquired glenoid bone loss and deformity is encountered in up to 40% of patients undergoing shoulder arthroplasty. 3,4 Increased complication and revision rates may be seen in this cohort due to compromised soft-tissue tensioning, glenoid instability and malalignment leading to early loosening, component impingement, and ultimately failure with reduced bone stock for subsequent revision. 5-10 Thus, the optimal surgical technique to reconstruct glenoid anatomy in rTSA remains an ongoing challenge in orthopaedic surgery.…”
Section: Introductionmentioning
confidence: 97%